Analysis of Green Marketing on Purchasing Decisions for Ades mineral water and Brand Image as an Intervening variable (Survey on Ades mineral water consumers in Sukabumi City) - Nashif Fauzan Abdillah; Asep Muhamad Ramdan; Resa Nurmala (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of Green Marketing on Purchasing Decisions for Ades mineral water, with Brand Image as the Intervening variable. In the context of increasing consumer awareness of environmental issues, marketing strategies that focus on sustainability are becoming increasingly important. The research method used was a survey with a questionnaire distributed to 210 respondents of Ades mineral water consumers in Sukabumi City. The data obtained were analyzed using path analysis to test the relationship between the variables studied. The results of this study indicate that Green Marketing has a positive and significant influence on Brand Image, and Brand Image has a positive effect on Purchasing Decisions. In addition, Brand Image is proven to act as an intervening variable that strengthens the relationship between Green Marketing and Purchasing Decisions. These findings indicate that effective Green Marketing strategies can enhance Brand Image and, in turn, influence Consumer Purchasing Decisions. This research provides insights for companies in designing marketing strategies that are more sustainable and responsive to the needs of consumers who care about the environment.